Peran Media Time Lines Chart Dalam Pembelajaran IPS di Sekolah Dasar - Nurulanjani, Dwilusiyana (Mimbar Sekolah Dasar, 2018)
Media plays an important role in the learning process. Many research results reveal the media give effect to the improvement of student learning outcomes. Initial findings of the research in Grade V SDN Sindangjati, Paseh-Sumedang showed that students have low historical thinking skills because the subject of history study in IPS subjects contains abstract facts, which are difficult to understand what made the students difficult to remember when and what happens in historical events as part of historical thinking skill. Efforts were made to overcome these problems by using the media timelines chart. The result of research using Classroom Action Research Method shows that the media timelines chart can increase the historical thinking skill.Â  The improvement can be seen from the increasing percentage of historical thinking skill in cycle I which was 62.50% then, becoming 87.50% in cycle II. It means that the media timelines chart in learning IPS material of Proclamation historical events can increase historical thinking skills. This means that the historical thinking test of social studies learning historical material of the Proclamation event has fulfilled the targeted objective of 84.38%.